Generation and characterization of a zebrafish gain-of-function ACOX1 Mitchell disease model - Quentin Raas; Quentin Raas; Austin Wood; Tamara J. Stevenson; Shanna Swartwood; Suzanne Liu; Rangaramanujam M. Kannan; Sujatha Kannan; Sujatha Kannan; Joshua L. Bonkowsky; Joshua L. Bonkowsky (Frontiers Media S.A., 2024)
BackgroundMitchell syndrome is a rare, neurodegenerative disease caused by an ACOX1 gain-of-function mutation (c.710A>G; p.N237S), with fewer than 20 reported cases. Affected patients present with leukodystrophy, seizures, and hearing loss. ACOX1 serves as the rate-limiting enzyme in peroxisomal beta-oxidation of very long-chain fatty acids. The N237S substitution has been shown to stabilize the active ACOX1 dimer, resulting in dysregulated enzymatic activity, increased oxidative stress, and glial damage. Mitchell syndrome lacks a vertebrate model, limiting insights into the pathophysiology of ACOX1-driven white matter damage and neuroinflammatory insults.MethodsWe report a patient presenting with rapidly progressive white matter damage and neurological decline, who was eventually diagnosed with an ACOX1 N237S mutation through whole genome sequencing. We developed a zebrafish model of Mitchell syndrome using transient ubiquitous overexpression of the human ACOX1 N237S variant tagged with GFP. We assayed zebrafish behavior, oligodendrocyte numbers, expression of white matter and inflammatory transcripts, and analysis of peroxisome counts.ResultsThe patient experienced progressive leukodystrophy and died 2 years after presentation. The transgenic zebrafish showed a decreased swimming ability, which was restored with the reactive microglia-targeted antioxidant dendrimer-N-acetyl-cysteine conjugate. The mutants showed no effect on oligodendrocyte counts but did display activation of the integrated stress response (ISR). Using a novel SKL-targeted mCherry reporter, we found that mutants had reduced density of peroxisomes.ConclusionsWe developed a vertebrate (zebrafish) model of Mitchell syndrome using transient ubiquitous overexpression of the human ACOX1 N237S variant. The transgenic mutants exhibited motor impairment and showed signs of activated ISR, but interestingly, there were no changes in oligodendrocyte counts. However, the mutants exhibited a deficiency in the number of peroxisomes, suggesting a possible shared mechanism with the Zellweger spectrum disorders.